CORRELATIONS BETWEEN THE INDEPENDENCE LEVEL OF ELDERLY AND DEPRESSION AT SENTRA TERPADU PANGUDI LUHUR - Rizki Faridho, Fikrifar (HEARTY, 2025)
Depression as one of the major mental health issue in the world is known to only 12.7% of sufferers who have received medical treatment, while the majority of them have not received it. The purpose of this study is to analyze the correlation between the independence level of the elderly and depression at Sentra Terpadu Pangudi Luhur (STPL). This study is a quantitative correlative study with a cross sectional approach using primary data from 68 respondents from Sentra Terpadu Pangudi Luhur (STPL) based on predetermined inclusion and exclusion criteria. Univariate analysis showed that most respondents experienced mild dependence (50%) but did not suffer from depression (75%). The results of the Spearman Rank correlation hypothesis test between the independence level of the elderly and depression showed a strong significant relationship in the negative direction (Correlation Coefficient -0.515) between the ADL Barthel Index score and the Geriatric Depression Scale-15 score. It means that the higher the level of dependence (not independent) of an elderly person, the higher the likelihood of depression. Currently, the elderly need a program to prevent dependency so that they can prevent depression in the future.